The Interpretation of Indexicals in Hybrid Quotation: A Pragmatic Account - Philippe De Brabanter (Anglophonia)
In this paper, I offer an analysis of a type of hybrid (including ‘mixed’, or ‘double-duty’) quotation that contains expressions indexed to a deictic centre distinct from the speaker of the host sentence, as in Trump insisted there was “zero chance I’ll quit”. Most writers on quotation offer a semantic account of hybrid quotation, in terms of the conventional meaning of some linguistic unit that occurs as part of the construction, usually quotation marks. Against these, and with Recanati (2000, 2001), I provide an analysis in terms of context-shifts. Understood in a broad sense, context can shift along several parameters: language, situation of utterance, circumstance of evaluation. I show that what is required in the case at hand is a situation-shift, and suggest how that shift can be articulated with other shifts. Relying on Clark & Gerrig (1990) and Clark (1996), I also show that shifts are selective and can therefore be partial. This further allows me to account for those less common hybrid quotations in which indexicals are indexed to the reporting context. All in all, my account points towards the viability of a pragmatic theory that views quotation as being a non-conventional, depictive act of communication, typically different from ordinary linguistic acts, the nature of which is essentially conventional.